Three-year follow-up analysis of axicabtagene ciloleucel in relapsed/refractory indolent non-Hodgkin lymphoma (ZUMA-5) - Neelapu, Sattva S; Chavez, Julio C; Sehgal, Alison R; Epperla, Narendranath; Ulrickson, Matthew; Bachy, Emmanuel; Munshi, Pashna N; Casulo, Carla; Maloney, David G; de Vos, Sven; Reshef, Ran; Leslie, Lori A; et al. (Blood, 2024)
Axicabtagene ciloleucel (axi-cel) is an autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy approved for relapsed/refractory (R/R) follicular lymphoma (FL). Approval was supported by the phase 2, multicenter, single-arm ZUMA-5 study of axi-cel for patients with R/R indolent non-Hodgkin lymphoma (iNHL; N = 104), including FL and marginal zone lymphoma (MZL). In the primary analysis (median follow-up, 17.5 months), the overall response rate (ORR) was 92% (complete response rate, 74%). Here, we report long-term outcomes from ZUMA-5. Eligible patients with R/R iNHL after ≥2 lines of therapy underwent leukapheresis, followed by lymphodepleting chemotherapy and axi-cel infusion (2 × 106 CAR T cells per kg). The primary end point was ORR, assessed in this analysis by investigators in all enrolled patients (intent-to-treat). After median follow-up of 41.7 months in FL (n = 127) and 31.8 months in MZL (n = 31), ORR was comparable with that of the primary analysis (FL, 94%; MZL, 77%). Median progression-free survival was 40.2 months in FL and not reached in MZL. Medians of overall survival were not reached in either disease type. Grade ≥3 adverse events of interest that occurred after the prior analyses were largely in recently treated patients. Clinical and pharmacokinetic outcomes correlated negatively with recent exposure to bendamustine and high metabolic tumor volume. After 3 years of follow-up in ZUMA-5, axi-cel demonstrated continued durable responses, with very few relapses beyond 2 years, and manageable safety in patients with R/R iNHL. The ZUMA-5 study was registered at www.clinicaltrials.gov as #NCT03105336.